2020
DOI: 10.3389/fphar.2020.607713
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Compounds With Glucocorticoid Sparing Effects on Suppression of Chemokine and Cytokine Production by Rheumatoid Arthritis Fibroblast-Like Synoviocytes

Abstract: In recent years target based drug discovery has expanded our therapeutic armamentarium in the treatment of inflammatory and autoimmune diseases. Despite these advances and adverse effects, glucocorticoids remain reliable agents that are used in many of these diseases. The anti-inflammatory mechanisms of glucocorticoids include the suppression of transcription factor activity like nuclear factor kappa B (NF-κB). By reanalyzing data from two prior high throughput screens (HTS) that utilized a NF-κB reporter cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…In the previous study, we identified that 5 μM of INH #1 suppressed 90% of NF-κB transcriptional activity 16 hours after the stimulation and the anti-inflammatory effects were saturated above 5 μM (Hosoya, T. et al, 2020). To explore the kinase inhibitory profile, we conducted 30 major serine/threonine-specific protein kinase assays, which were critical for cellular bioactivity (Table 1).…”
Section: 【Results】mentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous study, we identified that 5 μM of INH #1 suppressed 90% of NF-κB transcriptional activity 16 hours after the stimulation and the anti-inflammatory effects were saturated above 5 μM (Hosoya, T. et al, 2020). To explore the kinase inhibitory profile, we conducted 30 major serine/threonine-specific protein kinase assays, which were critical for cellular bioactivity (Table 1).…”
Section: 【Results】mentioning
confidence: 99%
“…These problems inspired us to develop agents that exhibit anti-inflammatory activity while retaining the physiologically essential bioactivities of NF-κB, which would enable us to address unmet needs for the treatment of inflammatory and autoimmune diseases. Toward this goal, we found a novel compound that inhibited inflammation-related NF-κB activity while retaining its physiological activity and with little cell toxicity using NF-κB reporter cells (Hosoya, T. et al, 2020).…”
Section: Downloaded Frommentioning
confidence: 99%
“…In order to further explore the functions of these exosome miRNAs and screen target miRNAs related to glucocorticoids, we performed KEGG and Go enrichment analyses of different miRNA target genes. The chemokine signaling pathway enriched by KEGG is closely related to the pharmacological action of glucocorticoids ( 26 , 27 ). The downstream protein of the chemokine signaling pathway is NFκB, and the anti-inflammatory effect of glucocorticoids is mainly achieved through the transcriptional inhibition of NFκB by GR ( 14 , 28 ).…”
Section: Discussionmentioning
confidence: 99%